Analysis of The Use Of SIASN in The Personnel and Human Resources Development Agency (BKPSDM) in Palangkaraya City Using The Hot Fit Approach - Mita Ashary; Ardieansyah Ardieansyah (Pt. Anagata Sembagi Education, 2025)
This study aims to examine how SIASN is utilized at the BKPSDM of Palangkaraya City. Based on the researcher's observations, the use of SIASN has not yet been explored in previous studies, making it the novelty of this research. The ASN Index Score (IP ASN) of Palangkaraya City ranked 17th with a